A comprehensive review of zebra chip disease in potato and its management through breeding for resistance/tolerance to 'Candidatus Liberibacter solanacearum' and its insect vector. Issue 9 (6th May 2022) - Prager, Sean M; Cohen, Abigail; Cooper, W Rodney; Novy, Richard; Rashed, Arash; Wenninger, Erik J; Wallis, Christopher
Abstract: Zebra chip disease (ZC), associated with the plant pathogenic bacterium ' Candidatus Liberibacter solanacearum' (psyllaurous) (CLso), is a major threat to global potato production. In addition to yield loss, CLso infection causes discoloration in the tubers, rendering them unmarketable. CLso is transmitted by the potato psyllid, Bactericera cockerelli (Šulc) (Hemiptera: Triozidae). ZC is managed by prophylactic insecticide applications to control the vector, which is costly and carries environmental and human health risks. Given the expense, difficulty, and unsustainability of managing vector‐borne diseases with insecticides, identifying sources of resistance to CLso and developing varieties that are resistant or tolerant to CLso and/or potato psyllids has become a major goal of breeding efforts. These efforts include field and laboratory evaluations of noncultivated germplasm and cultivars, studies of tubers in cold storage, detailed quantifications of biochemical responses to infection with CLso, possible mechanisms underlying insect resistance, and traditional examination of potato quality following infections. This review provides a brief history of ZC and potato psyllid, a summary of currently available tools to manage ZC, and a comprehensive review of breeding efforts for ZC and potato psyllid management within the greater context of Integrated Pest Management (IPM) strategies. © 2022 Society of Chemical Industry. This article has been contributed to by U.S. Government employees and their work is in the public domain in the USA. Abstract : Potato zebra chip disease is caused by Candidatus Liberibacter solanacearum and transmitted by potato psyllids. Management relies on insecticides and monitoring. We review efforts to produce resistant and tolerance varieties.